Outcomes in cardiogenic shock: the role of surrogate endpoints. Issue 4 (27th August 2022) - Kosyakovsky, Leah B.; Marbach, Jeffrey A.; Nguyen, Khoa; Mukundan, Srini; Chweich, Haval; Kapur, Navin K.
Abstract : Purpose of review: Early revascularization, invasive hemodynamic profiling, and initiation of temporary mechanical circulatory support (MCS) have all become routine components of cardiogenic shock (CS) management. Despite this evolution in clinical practice, patient selection and timing of treatment initiation remain a significant barrier to achieving sustained improvement in CS outcomes. Recent efforts to standardize CS management, through the development of treatment algorithms, have relied heavily on surrogate endpoints to drive therapeutic decisions. The present review aims to provide an overview of the basis of evidence for those surrogate endpoints commonly employed in clinical trials and CS management algorithms. Recent findings: Recent publications from both observational and randomized cohorts have demonstrated the utility of surrogate endpoints in risk stratifying patients with CS. In particular, invasive hemodynamics using pulmonary artery catheters to guide initiation and weaning of MCS, biochemical markers that portend imminent end-organ failure, and clinical risk scores that combine multiple hemodynamic and laboratory parameters have demonstrated an ability to prognosticate outcomes in patients with CS. Summary: Although further validation is necessary, multiple clinical, hemodynamic, and biochemical markers have demonstrated utility as surrogate endpoints in CS, and will undoubtedly assist physicians in clinical decision-making.